Aplikasi Teknologi Informasi Dan Komunikasi Guna Meningkatkan Proses Bisnis Organisasi Publik - Kristian Widya Wicaksono (Publica: Jurnal Pemikiran Administrasi Negara, 2020)
This paper aims to provide consideration for various local governments in Indonesia as a public organization, reflected on the success story of the Surabaya City Local Government, to incorporating information and communication technology in the structuring of the business processes of its organization. It is believed to improve the pace of decision-making and the responsiveness of public agencies to the public needs and demands. The method utilized in this paper is a systematic literature review that synthesizes and compares findings from previous research to generate new knowledge. The data used are secondary data collected from a wide range of literature which analyzed and evaluated quantitatively. The findings of this study indicate that the use of information and communication technology has a substantial effect on enhancing and improving the structuring of business processes in public organizations, i.e. (1) opening up cross-unit access of public institutions to data and information at the same time; (2) speeding up and simplifying the decision-making process; and (3) streamlining the public service delivery.